Tshoboko ya tiriso ya dipatlisiso tsa diphologolo tsa naga le tikologo mo Botswana (2) - Morrison, Monica; Botumile, Bontekanye (My University, 2021)
Translation from English to Setswana of complete abstract of the PhD thesis "The Uptake of Wildlife Research in Botswana: a Study of Productive Interactions" by Monica Morrison.
Related resources: - https://doi.org/10.6084/m9.figshare.14392991 - https://doi.org/10.6084/m9.figshare.14392988 - https://doi.org/10.6084/m9.figshare.14393177 - https://doi.org/10.6084/m9.figshare.14393225
Keywords: Setswana; wildlife research; Botswana